2-(x+3x-(x+6)-3)=3

Simple and best practice solution for 2-(x+3x-(x+6)-3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(x+3x-(x+6)-3)=3 equation:


Simplifying
2 + -1(x + 3x + -1(x + 6) + -3) = 3

Reorder the terms:
2 + -1(x + 3x + -1(6 + x) + -3) = 3
2 + -1(x + 3x + (6 * -1 + x * -1) + -3) = 3
2 + -1(x + 3x + (-6 + -1x) + -3) = 3

Reorder the terms:
2 + -1(-6 + -3 + x + 3x + -1x) = 3

Combine like terms: -6 + -3 = -9
2 + -1(-9 + x + 3x + -1x) = 3

Combine like terms: x + 3x = 4x
2 + -1(-9 + 4x + -1x) = 3

Combine like terms: 4x + -1x = 3x
2 + -1(-9 + 3x) = 3
2 + (-9 * -1 + 3x * -1) = 3
2 + (9 + -3x) = 3

Combine like terms: 2 + 9 = 11
11 + -3x = 3

Solving
11 + -3x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -3x = 3 + -11

Combine like terms: 11 + -11 = 0
0 + -3x = 3 + -11
-3x = 3 + -11

Combine like terms: 3 + -11 = -8
-3x = -8

Divide each side by '-3'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| 3-2/3x=x/2+1 | | 4(x-8)-2(x-5)+7x= | | (3v-2)(2v+1)=3v^2-11v-10 | | 4xy+3yz=-9xz-4xy | | 7.9x+1=6.9x | | 1/2x+2=(4x+1)/4 | | 18.1=p-7 | | v-9.85=6.4 | | 1/2x+2=4x+1/4 | | 27=2a+5 | | 10-x=17 | | 2xy+3yz=-5xz-2xy | | 4z-9z+2=0 | | -(8y+1)-(-7y-5)=5 | | x=-5x^2+6x+9 | | y(x)=-16x^2+64x | | a=2a+(-3) | | 500t=1000/300 | | x=-5x^2+8x+9 | | x^3+x^2+3*x+5=0 | | 2x-(5a+7x)=8x+(-3x+7a)-2a | | 3=j+2 | | f(x)=-5x^2+8x+9 | | 15(m+5)-3(8m+7)= | | 125x^2=12 | | -x^2-6x-8= | | -1=-5+I | | 6+2r-3=6r+3-3r | | 3[7x-2(y-1)]= | | 2=H-4 | | 2=H+4 | | u-1/8 |

Equations solver categories